الاثار الاجتماعية لما بعد كورونا وثقافة التباعد دراسة سوسيولوجيا في آثار جائحة كورونا: The social effects of post-COVID and the culture of distancing - الجواري, د احمد ياسين أحمد; د. احمد خضير حسين (Journal of College of Education, 2023)
The research aims to study the readiness of the Iraqi individual for social distancing in the face of the COVID-19 pandemic and shed light on the community's response to its danger. The study also examines the social dimensions of the culture of distancing on the individual and society. The research used a social survey method through a sample of 1500 respondents, and an electronic questionnaire was distributed randomly through online publication, covering all levels and statistically analyzed. The most important results of the field study are that social distancing due to the spread of COVID-19 has various positive and negative social effects. It has directly affected public health, personal hygiene, and leisure time availability, which helped intensify family relationships and return to personal relationships. Additionally, it has increased interest in technological development and constant search for alternatives to continue social life. However, it also has negative effects such as social isolation, loneliness, and the spread of psychological diseases.